Mapping Factors that Impact on Motivation of Undergraduate Students in Software Engineering: A case study - Schoeffel, Pablo; Ramos, Vinicius Faria Culmant; Wazlawick, Raul Sidnei; Vahldick, Adilson; Souza, Marcelo de (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2018: Anais do XXIX Simpósio Brasileiro de Informática na Educação, 2018)
This paper presents a case study with the evaluation of factors that impact on the motivation of 112 undergraduate students in a Software Engineering program. Considering that motivation and engagement are key aspects of students’ success, the goal of this paper is the identification of the factors that contribute to students' motivation and engagement. We applied a questionnaire which evaluates 48 motivational factors divided into 6 groups: personal and demographic data, general perception of motivation, perception about the university, student behavior, perception about program and perception about class/teacher. As results, after applying statistic tests, we found 15 factors with significant variance in the type of students’ motivation, only 3 factors with variance in the approval rate, and 5 factors with variance in the overall grade average. We conclude that, for the sample used, the perception of student behavior is associated with his/her performance. The type of motivation is associated mainly with the perception about the program, classes, and faculty. The intention of dropout is mainly associated with the perception of the classes and faculty.